The effect of low‐intensity extracorporeal shockwave therapy in an obesity‐associated erectile dysfunction rat model. (17th April 2018) - Ruan, Yajun; Zhou, Jun; Kang, Ning; Reed‐Maldonado, Amanda B.; Tamaddon, Arianna; Wang, Bohan; Wang, Hsun Shuan; Wang, Guifang; Banie, Lia; Lin, Guiting; Liu, Jihong; Lue, Tom F.
Abstract : Objectives: To investigate the feasibility of the Zucker fatty (ZF) rat as a model for research in to obesity‐associated erectile dysfunction (OAED) and to determine the effect of low‐intensity extracorporeal shockwave therapy (Li‐ESWT) on penile tissue and function in these rats. Materials and methods: Eight new‐born male Zucker lean (ZL group) rats (ZUC‐ Lepr fa 186) and 16 new‐born male ZF rats (ZUC‐ Lepr fa 185) were injected with 5‐ethynyl‐2'‐deoxyuridine (EdU) at birth to identify and monitor endogenous stem cells. Insulin tolerance testing was performed at 10 weeks of age. Beginning at 12 weeks of age, eight ZF rats were kept as controls, and the remaining eight ZF rats were treated with Li‐ESWT (0.02 mJ/mm 2, 3 Hz, 500 pulses; ZF + SW group) twice a week for 4 weeks. Following a 1‐week washout period, erectile function was evaluated by measuring intracavernosal pressure (ICP) and mean arterial pressure (MAP). Penile tissues were then harvested for histological study to assess smooth muscle/collagen content and endothelium content in the corpora cavernosum. LipidTOX™ staining was used to evaluate lipid accumulation. EdU, as a marker of cell activation, and phosphorylated histone 3 (H3P), as a marker of cell mitosis, were also assessed. Results: The ICP/MAP indicated that erectile function was severely impaired in the ZF group as compared with the ZL group. In the ZF + SW group, erectile function was significantly improved ( P < 0.05). Muscle atrophy was seen in the ZF group, while Li‐ESWT increased the muscle content in ZF + SW group. Moreover, the penile endothelium was damaged in the ZF group, and Li‐ESWT enhanced the regeneration of endothelial cells ( P < 0.01) in the ZF + SW group. Lipid accumulation was seen in the penile tissue of ZF rats. Li‐ESWT significantly reduced both the amount and the distribution pattern of LipidTOX, suggesting decreased overall lipid infiltration. Furthermore, Li‐ESWT increased EdU‐positive cells and markedly enhanced the phosphorylation level of H3P at Ser‐10 in the ZF + SW group. Most H3P‐positive cells were located within smooth muscle cells, with some located in the endothelium suggesting that these tissues are the reservoirs of penile stem/progenitor cells. Conclusion: ZF rats can serve as an animal model in which to study OAED. This study reveals that obesity impairs erectile function by causing smooth muscle atrophy, endothelial dysfunction, and lipid accumulation in the corpus cavernosum. Li‐ESWT restored penile haemodynamic parameters in the ZF rats by restoring smooth muscle and endothelium content and reducing lipid accumulation. The underlying mechanism of Li‐ESWT appears to be activation of stem/progenitor cells, which prompts cellular proliferation and accelerates penile tissue regeneration. Our findings are of interest, not just as a validation of this emerging treatment for erectile dysfunction, but also as a novel and potentially significant method to modulate endogenous stem/progenitor cells in other disease processes.